Conceptual Reconstruction and Epistemic Import: Allosteric Mechanistic Explanations as a Unified Theory-Net - Karina Alleva; José Díez; Lucía Federico (Crítica)
The goal of this article is to show that formal analysis and reconstructions may be useful to discuss and shed light on substantive meta-theoretical issues. We proceed here by exemplification, analysing and reconstructing as a case study a paradigmatic biochemical theory, the Monod-Wyman-Changeux (MWC) theory of allosterism, and applying the reconstruction to the discussion of some issues raised by prominent representatives of the new mechanist philosophy. We conclude that our study shows that at least in this case mechanicism and (some version of) more traditional accounts are not rivals but complementary approaches.